Positive electrode material, preparation method thereof and battery

By using the pulse sintering and dissociation treatment technology of the mixture during the preparation of the positive electrode material, the number of agglomerates and particle morphology are controlled, and the battery performance deterioration caused by the agglomerates of the positive electrode material is solved, and the capacity and circulation performance are improved.

CN119764392APending Publication Date: 2025-04-04SHENZHEN CITY BATTERY NANOMETER TECH

Patent Information

Application Number
CN202411950144.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing cathode materials are prone to agglomerates during high-temperature sintering, resulting in deterioration of battery performance and affecting capacity and long cycle stability.

Method used

By mixing the oxide precursor, lithium source, dopant and pore-forming agent, and performing pulse sintering treatment under an oxygen-containing atmosphere, followed by dissociation and secondary sintering treatment, the proportion of the number of agglomerates is less than 1%, ensuring that the average aspect ratio of the particles is within the range of 1-1.6.

Benefits of technology

It effectively reduces agglomerates in the cathode material, improves capacity and long circulation performance, and improves particle structure strength and compaction density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764392A_ABST
    Figure CN119764392A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material, a preparation method thereof and a battery. The positive electrode material comprises a plurality of particles and aggregate particles, an SEM image of the positive electrode material is measured under the amplification factor of 3K through a scanning electron microscope, the total number of particles of the positive electrode material in the SEM image is N, N is larger than or equal to 200, and the number of aggregate particles formed by aggregating 5 or more particles with the particle size smaller than 1 micron is n; the number ratio beta of the aggregates is n / N, and beta is less than or equal to 1%; more than 200 particles in the SEM image are randomly measured, the average size of the longest diameter of a single particle is D, the average size of the width diameter of the longest diameter of the vertically equally divided particle is L, the average length-diameter ratio alpha of the particles is equal to D / L, and alpha is more than 1 and less than 1.6. According to the positive electrode material, the lithium ion transmission efficiency can be improved, the long cycle performance of the positive electrode material is improved, and the gas production phenomenon of the positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and preparation methods thereof, and batteries. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, high power density, long cycle life and low self-discharge, so they are widely used in 3C electronic products, electric vehicles and energy storage. As the core component of lithium-ion batteries, the positive electrode material directly determines the operating voltage and storage capacity of the battery.

[0003] At present, commercial cathode materials are made by mixing coprecipitation precursors with lithium sources, and then undergoing sintering, crushing, airflow milling, coating, screening and demagnetization processes. Since coprecipitation precursors are mostly spherical, agglomerates are easily generated during high-temperature sintering. During the rolling process of the battery pole piece, the agglomerate particles are easily crushed, and the exposed surface of the cathode material particles is in direct contact with the electrolyte during the charge and discharge process, resulting in an increase in surface side reactions, which leads to deterioration of battery performance and affects the capacity of the cathode material.

[0004] Therefore, how to reduce the agglomerates in the positive electrode materials and improve the capacity and long-cycle stability of the positive electrode materials is still an urgent problem to be solved. Summary of the invention

[0005] The present application provides a positive electrode material and a preparation method thereof, and a battery. The positive electrode material of the present application can reduce agglomerates in the positive electrode material and improve the capacity and long-cycle stability of the positive electrode material.

[0006] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a plurality of particles and agglomerated particles;

[0007] The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, the total number of particles of the positive electrode material in the SEM image is N, N ≥ 200, wherein the number of agglomerate particles formed by agglomeration of 5 or more particles with a particle size of less than 1 μm is n;

[0008] The number ratio of the agglomerates β=n / N, β≤1%;

[0009] More than 200 particles in the SEM image are randomly measured, the average size of the longest diameter of a single particle is D, the average size of the straight line side perpendicularly bisecting the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1<α<1.6.

[0010] In some embodiments, 2.0 μm<D<3.0 μm; 1.5 μm≤L≤2.5 μm.

[0011] In some embodiments, the chemical formula of the positive electrode material is Li k Ni a Co b N c M d O 2 , 0.98≤k≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, M is a metal element, and the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La and Ce.

[0012] In some embodiments, the volume median particle size D50 of the positive electrode material is 3.0 μm to 5.0 μm.

[0013] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 1.0<(D 90 -D 10 ) / D 50 <1.5.

[0014] In some embodiments, the positive electrode material is a single crystal material, the particles include primary particles, the primary particles have the same orientation, and the particle size of the primary particles is 1 μm to 5 μm.

[0015] In some embodiments, the specific surface area of ​​the positive electrode material is S m 2 / g, 0.5<S<0.9.

[0016] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 1.8<ρ1<2.5.

[0017] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 3<ρ2<3.5.

[0018] In some embodiments, the longest length of the agglomerates is less than 4 μm.

[0019] In a second aspect, the present application provides a method for preparing a positive electrode material, the preparation method comprising:

[0020] Mixing an oxide precursor, a lithium source, a dopant and a pore former to obtain a first mixture, wherein the amount of the pore former added is 1% to 5% based on the mass of the oxide precursor being 100%;

[0021] In an oxygen-containing atmosphere, the first mixture is pulse sintered to obtain a matrix material, wherein the pulse sintering process includes a first stage, a second stage, the first stage and the second stage repeated, and a fifth stage, and the sintering temperature T of the first stage is 1 The sintering temperature of the second stage is 800℃~1000℃. 2 T 1 -30°C, the sintering temperature T of the fifth stage 5 T 2 -10℃; control T 1 The total temperature holding time is 4h to 8h;

[0022] The base material is subjected to a dissociation treatment, and after the dissociation product is mixed with a coating agent, a secondary sintering treatment is performed to obtain a positive electrode material.

[0023] In some embodiments, the oxide precursor has a general chemical formula of Ni x Co y N z M e O 2 , wherein 0.50≤x≤0.98, 0<y≤0.20, 0<z≤0.35, 0≤e≤0.05, x+y+z+e=1, and N is Mn or Al.

[0024] In some embodiments, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal in the oxide precursor is 1.0≤n Li / n Me ≤1.06.

[0025] In some embodiments, based on 100% by mass of the oxide precursor, the amount of the dopant added is 0.05% to 0.4%.

[0026] In some embodiments, the pore former includes at least one of carbon powder, sucrose, starch, pine powder, polyvinyl alcohol, polymethyl methacrylate, polyethylene glycol and coal powder.

[0027] In some embodiments, the dopant includes a compound containing element M, and the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La and Ce.

[0028] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium acetate, lithium phosphate, and lithium oxalate.

[0029] In some embodiments, the dissociation treatment includes at least one of roller crushing, mechanical pulverization, air flow pulverization and micron-sized particle dissociation.

[0030] In some embodiments, the dissociation treatment includes air flow milling, and the grinding air pressure of the air flow milling is 0.3Mpa to 0.8Mpa.

[0031] In some embodiments, the dissociation treatment includes air flow pulverization, and the classification frequency of the air flow pulverization is 30 Hz to 55 Hz.

[0032] In some embodiments, the secondary sintering process is performed at a temperature of 350° C. to 600° C. for a time of 5 h to 10 h.

[0033] In a third aspect, the present application provides a battery, comprising the positive electrode material described in the first aspect.

[0034] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0035] The average aspect ratio of the particles of the positive electrode material of the present application is within the above range, which can improve the problem of excessive local expansion stress and slow down the diffusion of particle cracks caused by local expansion, thereby reducing the side reactions between the positive electrode material and the electrolyte and improving the long cycle performance; however, as the roundness of the particles increases, the fine powder decreases, and the volume particle size distribution of the positive electrode material narrows, the compaction density of the positive electrode material decreases and the capacity decreases. Therefore, while controlling the average aspect ratio of the positive electrode material particles, the present application controls the number of agglomerates to account for less than 1%. The synergistic effect of the two can significantly reduce the particle rupture phenomenon during the rolling process, reduce the consumption of active lithium ions, and improve the particle structure strength of the positive electrode material. A small amount of agglomerates can improve the compaction density and capacity of the positive electrode material, and comprehensively improve the long cycle performance of the positive electrode material.

[0036] The preparation method of the positive electrode material provided in the present application is to mix an oxide precursor, a lithium source, a dopant and a pore-forming agent. The addition of the pore-forming agent is conducive to the precursor being fully in contact with oxygen during the sintering process, accelerating the reaction rate, increasing the looseness of the matrix material, and reducing the degree of agglomeration of the particles, so that the proportion of the number of agglomerates in the positive electrode material is also greatly reduced, and the roundness of the particles in the matrix material can also be improved. At the same time, a pulse sintering process is adopted. Due to the short high-temperature sintering time, the particles tend to grow uniformly, and the average aspect ratio of the sintered particles can be controlled within an appropriate range. The matrix material undergoes dissociation treatment, in which some agglomerates formed by 2 to 3 particles can be dissociated again into single particles during the dissociation process, which can reduce the proportion of agglomerates in the positive electrode material. During the secondary sintering process of these particles with exposed surfaces, the coating agent can form a coating material on the surface of the particles, reduce the surface residual alkali of the positive electrode material, and further improve the tolerance and structural order of the particles of the positive electrode material, improve the cation mixing phenomenon, thereby improving the compaction density and capacity of the positive electrode material, and at the same time improving the long cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0038] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application;

[0039] Figure 2 This is a SEM morphology of the positive electrode material provided in Example 1 of the present application;

[0040] Figure 3 This is a SEM morphology image of the positive electrode material provided in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0041] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0042] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0044] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0045] The inventors found that at present, the positive electrode material is prepared by mixing the coprecipitation precursor with the lithium source, and then undergoing sintering, crushing, airflow crushing, coating, screening and demagnetization. Since the coprecipitation precursors are mostly spherical, agglomerates are easily generated during the high-temperature sintering process. During the rolling process of the battery pole piece, the agglomerate particles are easily crushed, and the exposed surface of the positive electrode material particles is in direct contact with the electrolyte during the charge and discharge process, which increases the surface side reactions, resulting in the degradation of battery performance and affecting the capacity of the positive electrode material.

[0046] Therefore, how to reduce the agglomerates in the positive electrode materials and improve the capacity and long-cycle stability of the positive electrode materials is still an urgent problem to be solved.

[0047] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a plurality of particles and agglomerated particles;

[0048] The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, the total number of particles of the positive electrode material in the SEM image is N, N ≥ 200, wherein the number of agglomerate particles formed by agglomeration of 5 or more particles with a particle size of less than 1 μm is n;

[0049] The number ratio of the agglomerates β=n / N, β≤1%;

[0050] More than 200 particles in the SEM image are randomly measured, the average size of the longest diameter of a single particle is D, the average size of the straight line side perpendicularly bisecting the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1<α<1.6.

[0051] The positive electrode material provided by the present application has an average aspect ratio of the particles of the positive electrode material within the above range, which slows down the diffusion of particle cracks caused by local expansion, thereby reducing the side reactions of the positive electrode material with the electrolyte and improving the long cycle performance. When the average aspect ratio of the particles of the positive electrode material is too large, it means that the particles have poor roundness and obvious edges and corners. It is easy to produce more fine powder during the particle shaping process, resulting in an increase in the specific surface area of ​​the positive electrode material and an increase in the side reactions with the electrolyte. In addition, particles with poor roundness are prone to excessive local expansion pressure during the charge and discharge cycle, and tiny cracks are also easily generated inside the particles, and even cause particle rupture, which reduces the structural stability and cycle stability of the positive electrode material.

[0052] However, as the roundness of the particles increases, the amount of fine powder decreases, and the volume particle size distribution of the positive electrode material narrows, the compaction density of the positive electrode material decreases and the capacity decreases. Therefore, while controlling the average aspect ratio of the positive electrode material particles, the present application controls the number of agglomerates to be less than 1%. The synergistic effect of the two can significantly reduce the particle breakage phenomenon during the rolling process, reduce the consumption of active lithium ions, and improve the particle structure strength of the positive electrode material. In addition, a small amount of agglomerates can improve the compaction density and capacity of the positive electrode material, and comprehensively improve the long cycle performance of the positive electrode material.

[0053] In some embodiments, the positive electrode material is a lithium nickel cobalt oxide compound, and the chemical formula of the positive electrode material is Li k Ni a Co b N c M d O 2 , 0.98≤k≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al.

[0054] The specific value of k can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the specific value of a can be 0.5, 0.6, 0.7, 0.8, 0.82, 0.84, 0.85, 0.88, 0.89, 0.90, 0.92, 0.95 or 0.98, and the value of b can be 0.001, 0.01, 0.05, 0.1, 0.1 The value of c can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.18, 0.2, 0.25, 0.3 or 0.35, and the value of d can be 0, 0.001, 0.005, 0.006, 0.008, 0.009, 0.01, 0.02, 0.03, 0.05, 0.07 or 0.1, etc., and is not limited here.

[0055] In some embodiments, the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La, and Ce. It can be understood that the M element doped in the positive electrode material can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing.

[0056] In some embodiments, the number of agglomerates accounts for β≤1%, and β can specifically be 1%, 0.9%, 0.8%, 0.7%, 0.6%, 0.5%, 0.3%, 0.2%, 0.1%, 0.05%, etc., and of course it can also be other values ​​within the above range, which is not limited here. When β>1%, it means that the number of agglomerates of the particles increases. Although the compaction density of the positive electrode material can be improved, the compaction density of the positive electrode sheet decreases due to the low particle strength of the agglomerates. During the rolling process of the electrode sheet, the agglomerates are easily broken, the exposed surface of the positive electrode material increases, and the side reactions with the electrolyte increase, which affects the capacity of the positive electrode material and the long-cycle stability. The present application controls the number of agglomerates to account for β≤1%. The particle strength of the positive electrode material is relatively high, which can reduce the particle breakage phenomenon during the rolling process of the electrode sheet, and the exposed surface of the fine powder and particles is greatly reduced, thereby improving the gas production phenomenon. Moreover, the positive electrode material has good particle dispersion, which enables the compaction density of the positive electrode material to be maintained at a high level, thereby improving the capacity and long cycle performance of the positive electrode material. It should be noted that the agglomerate refers to agglomerate particles formed by the agglomeration of 5 or more particles with a particle size of less than 1 μm. In the SEM image, the longest length of the agglomerate is less than 4 μm.

[0057] In some embodiments, the size of the particles satisfies: 2.0 μm < D < 3.0 μm; 1.5 μm ≤ L ≤ 2.5 μm. The value of D can be 2.1 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm or 2.9 μm, etc., and of course it can also be other values ​​within the above range, which is not limited here. The value of L can be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm or 2.5 μm, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0058] In some embodiments, the average aspect ratio of the particles satisfies 1<α<1.6, which may be 1.1, 1.2, 1.3, 1.4, 1.5 or 1.59, etc. Of course, it may also be other values ​​within the above range, which is not limited here. The average aspect ratio of the particles is within the above range, which can improve the problem of excessive local expansion stress and slow down the diffusion of particle cracks caused by local expansion, thereby reducing the side reactions of the positive electrode material and the electrolyte, and improving the long cycle performance. When the aspect ratio of the particles is too large, it means that the particles have poor roundness and obvious edges and corners. It is easy to produce more fine powder during the air flow crushing of the positive electrode material particles, resulting in an increase in the specific surface area of ​​the positive electrode material and an increase in the side reactions with the electrolyte. In addition, particles with poor roundness are prone to excessive local expansion pressure during the charge and discharge cycle, and tiny cracks are also easily generated inside the particles, and even cause the particles to rupture, which reduces the structural stability and cycle stability of the positive electrode material.

[0059] In some embodiments, the volume median particle size D50 of the positive electrode material is 3.0 μm to 5.0 μm, specifically 3.0 μm, 3.2 μm, 3.5 μm, 4.0 μm, 4.3 μm, 4.5 μm, 4.8 μm or 5.0 μm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Since most of the particles in the positive electrode material are particles, that is, the median particle size of the particles is within the above range, the particles within this size range have better electrochemical properties, higher discharge capacity and excellent rate performance.

[0060] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 1.0<(D 90 -D 10 ) / D 50 <1.5, specifically can be 1.05, 1.08, 1.1, 1.15, 1.18, 1.2, 1.22, 1.25, 1.26, 1.28, 1.3, 1.35, 1.4 or 1.49, etc., of course, it can also be other values ​​within the above range, which are not limited here. In the present application, by controlling the particle size distribution width of the positive electrode material within the above range, particles of different sizes can be stacked more closely, so that the compaction density of the positive electrode sheet is improved and the energy density is higher.

[0061] In some embodiments, the positive electrode material is a single crystal material, the particles include primary particles, the primary particles have the same orientation, and the particle size of the primary particles is 1 μm to 5 μm.

[0062] It should be specifically pointed out that the "grains with the same orientation" known to those skilled in the art are not "single crystals" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in reality. Therefore, the materials known in the art that have a single crystal structure are actually more of a "single crystal-like morphology" positive electrode material, which only shows a single crystal-like large particle size in size, which is different from the polycrystalline particles composed of many small particles.

[0063] The particles with the same orientation in the present application can be a single particle composed of one primary particle. The above-mentioned single crystal positive electrode material can also contain a small amount of "quasi-secondary particles" formed by the adhesion of several primary particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope.

[0064] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one primary particle is the same, so as to judge that the orientation in at least one primary particle is the same, and the primary particles with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0065] In some embodiments, the specific surface area of ​​the positive electrode material is S m 2 / g, 0.5<S<0.9; specifically, it can be 0.51m 2 / g, 0.55m 2 / g, 0.58m 2 / g, 0.6m 2 / g, 0.65m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.8m 2 / g, 0.85m 2 / g or 0.89m 2 / g, etc., and of course, other values ​​within the above range may also be possible, which are not limited here. Controlling the specific surface area of ​​the positive electrode material within the above range can effectively control the side reaction between the positive electrode material and the electrolyte, and improve the capacity of the positive electrode material.

[0066] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 1.8<ρ1<2.5, specifically 1.82g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 、1.98g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 or 2.49 g / cm 3 Etc., of course, it can also be other values ​​within the above range, which are not limited here. When the tap density of the positive electrode material is too small, the compaction density of the positive electrode sheet prepared from the positive electrode material decreases, and the particle strength is also relatively reduced, resulting in a decrease in the energy density of the lithium-ion battery. When the tap density of the positive electrode material is too large, the compaction density of the positive electrode sheet prepared from the positive electrode material is too high, and the porosity of the positive electrode sheet decreases, which will make it difficult for the electrolyte to effectively infiltrate the sheet, increase the internal resistance of the lithium-ion battery, and decrease the gram capacity of the positive electrode material. The present application controls the tap density of the positive electrode material within the above range, which can be beneficial to improving the energy density of the positive electrode sheet.

[0067] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 3<ρ2<3.5. Specifically, it can be 3.05g / cm 3 、3.1g / cm 3 、3.15g / cm 3 、3.18g / cm 3 、3.2g / cm 3 , 3.25g / cm 3 、3.3g / cm 3 、3.35g / cm 3 、3.4g / cm 3 、3.45g / cm 3 、3.48g / cm3 or 3.49 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here. The present application controls the compaction density of the positive electrode material within the above range, which is beneficial to the performance of the positive electrode material capacity, improves the energy density, improves the polarization phenomenon of the battery prepared by the positive electrode material during the cycle, and is beneficial to improve the capacity retention rate of the battery.

[0068] In some embodiments, the mass content of the surface residual alkali in the positive electrode material is m Li wt%0.10<m Li <0.25,m Li Specifically, it can be 0.11wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.20wt%, 0.22wt%, 0.23wt% or 0.24wt%, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. It can be understood that the surface alkaline impurities of the positive electrode material mainly refer to Li 2 CO 3 and LiOH. The residual alkali on the surface of the positive electrode material (LiOH and Li 2 CO 3 ) is controlled within the above range, which can reduce the corrosion effect of alkaline substances on the positive electrode material, protect the structural stability of the positive electrode material, and is beneficial to improving the cycle stability of the positive electrode material.

[0069] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0070] Step S100, mixing an oxide precursor, a lithium source, a dopant and a pore-forming agent to obtain a first mixture, wherein the amount of the pore-forming agent added is 1% to 5% based on the mass of the oxide precursor as 100%;

[0071] Step S200, in an oxygen-containing atmosphere, subjecting the first mixture to a pulse sintering process to obtain a matrix material, wherein the pulse sintering process includes a first stage, a second stage, and the first stage and the second stage being repeated in sequence, and the sintering temperature T of the first stage is 1 The sintering temperature of the second stage is 800℃~1000℃. 2 T 1 -30℃, control T 1 The total temperature holding time is 4h to 8h;

[0072] Step S300, dissociating the base material, mixing the dissociation product with the coating agent, and then performing a secondary sintering process to obtain a positive electrode material.

[0073] The preparation method of the positive electrode material provided in the present application is to mix an oxide precursor, a lithium source, a dopant and a pore-forming agent. The addition of the pore-forming agent is conducive to the precursor being fully in contact with oxygen during the sintering process, accelerating the reaction rate, increasing the looseness of the matrix material, and reducing the degree of agglomeration of the particles, so that the proportion of the number of agglomerates in the positive electrode material is also greatly reduced, and the roundness of the particles in the matrix material can also be improved. At the same time, a pulse sintering process is adopted. Due to the short high-temperature sintering time, the particles tend to grow uniformly, and the average aspect ratio of the sintered particles can be controlled within an appropriate range. The matrix material undergoes dissociation treatment, in which some agglomerates formed by 2 to 3 particles can be dissociated again into single particles during the dissociation process, which can reduce the proportion of agglomerates in the positive electrode material. During the secondary sintering process of these particles with exposed surfaces, the coating agent can form a coating material on the surface of the particles, reduce the surface residual alkali of the positive electrode material, and further improve the tolerance and structural order of the particles of the positive electrode material, improve the cation mixing phenomenon, thereby improving the compaction density and capacity of the positive electrode material, and at the same time improving the long cycle performance of the positive electrode material.

[0074] The preparation method of the present application is described in detail below in conjunction with the above embodiments:

[0075] Before step S100, the method further includes: preparing a salt solution of nickel, manganese and N elements into a mixed solution according to a certain stoichiometric ratio, and preparing an oxide precursor by a spray pyrolysis method, wherein the N element is Mn or Al.

[0076] In some embodiments, the stoichiometric ratio range between nickel, cobalt and N elements meets the following conditions: 0.5≤Ni≤0.98, 0<Co≤0.2, 0<Mn≤0.35; the molar ratio of Ni:Co:Mn can be specifically 0.60:0.10:0.30, 0.67:0.05:0.28 or 0.90:0.5:0.05, etc.

[0077] In some embodiments, the salt solution is at least one of nitrate, hydrochloride, sulfate, carbonate, oxalate, and acetate. For example, the nickel salt solution can be at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate. Of course, nickel, manganese, aluminum, and cobalt can also be metal elemental raw materials or recycled materials of ternary positive electrode materials, which are not limited here.

[0078] In some embodiments, a compound containing element M is further added to the salt solution according to a target doping ratio, which may specifically be a nitrate containing element M, a hydrochloride containing element M, an acid containing element M, etc., which is not limited here.

[0079] In some embodiments, the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La, and Ce.

[0080] In some embodiments, the spray pyrolysis includes a dehydration stage and a pyrolysis stage, wherein the temperature of the dehydration stage is 300°C to 500°C, and the temperature of the pyrolysis stage is 500°C to 850°C.

[0081] Specifically, the temperature in the dehydration stage can be 300°C, 350°C, 380°C, 400°C, 430°C, 450°C or 500°C, etc., and of course it can also be other values ​​within the above range, which is not limited here. The temperature in the pyrolysis stage can be 510°C, 520°C, 530°C, 550°C, 600°C, 650°C, 680°C, 700°C, 750°C, 800°C or 850°C, etc., and of course it can also be other values ​​within the above range, which is not limited here. In the dehydration temperature zone, the mixed solution after spray atomization treatment is rapidly dehydrated, and in the pyrolysis temperature zone, the dehydrated particles are finally pyrolyzed into oxide precursor particles.

[0082] In some embodiments, the product of spray pyrolysis is subjected to airflow pulverization to control the oxide precursor D50 to be 2.0 μm to 4.0 μm, specifically 2.0 μm, 2.2 μm, 2.5 μm, 3.0 μm, 3.3 μm, 3.5 μm, 3.8 μm or 4.0 μm, etc., and of course other values ​​within the above range can also be used.

[0083] In some embodiments, the oxide precursor has a general chemical formula of Ni x Co y N z M e O 2 , wherein 0.50≤x≤0.98, 0<y≤0.20, 0<z≤0.35, 0≤e≤0.05, x+y+z+e=1, and N is Mn or Al.

[0084] Step S100 , mixing an oxide precursor, a lithium source, a dopant and a pore former to obtain a first mixture, wherein the amount of the pore former added is 1% to 5% based on the mass of the oxide precursor being 100%.

[0085] In some embodiments, the amount of pore former added can be 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. If too little pore former is added, the growth process of the positive electrode material particles is greatly affected by the sintering conditions such as atmosphere and temperature, which can easily lead to insufficient particle growth, obvious edges and corners, and increased soft agglomeration, thereby affecting the cycle performance. If too much pore former is added, the positive electrode material particles grow uniformly, the volume distribution width of the positive electrode material is narrowed, and the compaction density decreases, affecting the capacity.

[0086] In some embodiments, the pore former includes at least one of carbon powder, sucrose, starch, pine powder, polyvinyl alcohol, polymethyl methacrylate, polyethylene glycol and coal powder.

[0087] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate, and lithium oxalate.

[0088] In some embodiments, the ratio of the molar amount of Li in the lithium source to the total molar amount of the transition metal in the oxide precursor is controlled to be 1.0≤n Li / n Me ≤1.06; specifically, it can be 1.0:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1 or 1.06:1, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0089] In some embodiments, the amount of dopant added is 0.05% to 0.4%, specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.28%, 0.3%, 0.35% or 0.4%, etc., based on the mass of the oxide precursor as 100%, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The amount of dopant added in the present application is controlled within the above range, which is conducive to controlling the size of the positive electrode material particles and the arrangement of the particles, and improving the capacity of the positive electrode material and the stability of the particle structure.

[0090] In some embodiments, the mixing is performed in a mixing device, which may be a high mixer, a ball mill mixer, a VC mixer, or a three-dimensional mixer, etc., which may be selected according to actual needs and is not limited here. It can be understood that by fully mixing, it is beneficial to improve the distribution uniformity of the oxide precursor and the lithium source, to reduce the structural defects in the positive electrode material, and to improve the structural orderliness of the positive electrode material.

[0091] Step S200, in an oxygen-containing atmosphere, subjecting the first mixture to a pulse sintering process to obtain a matrix material, wherein the pulse sintering process includes a first stage, a second stage, the first stage and the second stage repeated, and a fifth stage, and the sintering temperature of the first stage is T 1 The sintering temperature of the second stage is 800℃~1000℃. 2 T 1 -30°C, the sintering temperature T of the fifth stage 5 T 2 -10℃; control T 1 The total temperature holding time is 4h to 8h.

[0092] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.

[0093] In some embodiments, the heating rate of the pulse sintering process is 0.5°C / min to 2.5°C / min, specifically 0.5°C / min, 0.75°C / min, 1°C / min, 1.25°C / min, 1.5°C / min, 2°C / min, 2.25°C / min or 2.5°C / min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0094] In some embodiments, during the pulse sintering process, the ambient pressure is 20Pa to 60Pa, specifically 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, 50Pa, 55Pa or 60Pa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0095] In some embodiments, during the pulse sintering process, the sintering temperature T in the first stage is 1 It is 800℃~1000℃, specifically can be 800℃, 820℃, 830℃, 850℃, 870℃, 900℃, 950℃, 980℃, 990℃ or 1000℃, etc., of course, it can also be other values ​​within the above range, which is not limited here.

[0096] In some embodiments, the holding time of the first stage of the pulse sintering process is 1 h to 2 h, specifically 1.0 h, 1.2 h, 1.5 h or 2 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0097] In some embodiments, the sintering temperature T of the second stage is 2 T 1-30°C, specifically it can be 770°C, 820°C, 850°C, 870°C, 900°C, 950°C or 970°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0098] In some embodiments, the insulation time of the second stage is 1 h to 2 h, specifically 1.0 h, 1.2 h, 1.5 h or 2 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0099] In some embodiments, during the entire pulse sintering process, T 1 The total temperature holding time is 4h to 8h, and can be specifically 4.0h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0100] In some embodiments, during the pulse sintering process, the sintering temperature T 4 T 2 -10℃, i.e. 760℃~960℃, specifically it can be 760℃, 820℃, 850℃, 870℃, 900℃, 950℃ or 960℃, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0101] In some embodiments, the insulation time of the fourth stage is 4 h to 6 h, specifically 4 h, 4.5 h, 5 h, 5.5 h, 5.8 h or 6 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0102] The temperature and time of the fourth stage of the pulse sintering treatment are controlled within the above range, which can promote the repair of the grain boundary surface of the positive electrode material and improve the particle tolerance and structural order of the positive electrode material.

[0103] Step S300, dissociating the base material, mixing the dissociation product with the coating agent, and then performing a secondary sintering process to obtain a positive electrode material.

[0104] In some embodiments, the dissociation treatment includes at least one of roller crushing, mechanical pulverization, air flow pulverization and micron-sized particle dissociation.

[0105] In some embodiments, the dissociation treatment includes air flow grinding, and the grinding air pressure of the air flow grinding is 0.3Mpa to 0.8Mpa, specifically 0.3Mpa, 0.4Mpa, 0.5Mpa, 0.55Mpa, 0.6Mpa, 0.65Mpa, 0.7Mpa or 0.8Mpa, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0106] In some embodiments, the classification frequency of air flow milling is 30 Hz to 55 Hz, and can be specifically 30 Hz, 35 Hz, 40 Hz, 45 Hz, 50 Hz or 55 Hz, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0107] In some embodiments, the number of aggregates in the dissociation product accounts for ≤1%, and can be specifically 1%, 0.9%, 0.8%, 0.7%, 0.6%, 0.5%, 0.3%, 0.2%, 0.1%, 0.05%, etc., and of course can also be other values ​​within the above range, which are not limited here.

[0108] The present application can reduce the proportion of agglomerates in the positive electrode material by controlling the grinding air pressure and grading frequency during air flow milling. Some agglomerates formed by the agglomeration of 2 to 3 primary particles can be dissociated into single particles during the dissociation process. During the secondary sintering process, the coating agent can form a coating layer on the surface of these particles with exposed surfaces, thereby reducing the surface residual alkali of the positive electrode material, further improving the tolerance and structural order of the particles of the positive electrode material, and improving the cation mixing phenomenon.

[0109] In some embodiments, the median particle size of the dissociation product is ≤ 5 μm.

[0110] In some embodiments, based on the mass of the dissociation product as 100%, the amount of the coating agent added is 0.1% to 0.8%, specifically 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7% or 0.8%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some embodiments, the coating agent includes a compound containing an M element, and the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La and Ce.

[0112] In some embodiments, the capping agent comprises La(NO 3 ) 3 6H 2 O、(NH 4 )HB 4 O 7 NH 4 ) 2 MoO 4 , H 3 BO 3 NH 4 ) 6 W7 O 24 6H 2 O、(NH 4 ) 3 PW 12 O 40 ·3H 2 O、Zr(SO 4 ) 2 ·4H 2 O, H 28 N 6 O 41 W 12 , WO 3 and Al 2 O 3 At least one. It should be noted that due to H 28 N 6 O 41 W 12 It is difficult to dissolve in water, so H 28 N 6 O 41 W 12 When H 28 N 6 O 41 W 12 Dry mix directly with base material.

[0113] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.

[0114] In some embodiments, the temperature of the secondary sintering treatment is 350°C to 600°C, specifically 350°C, 360°C, 380°C, 400°C, 420°C, 480°C, 500°C, 550°C or 600°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0115] In some embodiments, the secondary sintering treatment time is 5 h to 10 h, specifically 5 h, 5.5 h, 6 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0116] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.

[0117] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.

[0118] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.

[0119] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.

[0120] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0121] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .

[0122] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.

[0123] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.

[0124] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0125] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0126] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0127] The technical solution of the present application is further described below in conjunction with embodiments:

[0128] Example 1

[0129] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=60:10:30, and then a hydrochloride solution of 0.2% Zr and a hydrochloride solution of 0.05% Sr and 0.05% Ca were added to the mixed solution.

[0130] (2) The positive electrode material precursor (Ni) was synthesized by spray pyrolysis method (dehydration temperature 500°C, pyrolysis temperature 650°C) 0.6 Co 0.1 Mn 0.3 O, because the amount of doping elements Zr, Sr, Ca is difficult to determine accurately, it is not reflected in the chemical formula), the positive electrode material precursor is air flow crushed to obtain an oxide precursor with a particle size D50 = 3.3 μm.

[0131] (3) Mix the oxide precursor with Li 2 CO 3 According to the molar ratio of 1:1.03, the oxide precursor and sucrose are evenly mixed in a mass ratio of 1:3% to obtain a first mixture, and the first mixture is subjected to pulse sintering treatment in an oxygen atmosphere with an ambient pressure of 40 Pa. The specific sintering process is as follows: the temperature T1 of the first sintering stage is 970°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 940°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 970°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 970°C, and the holding time t4 is 2h. 4 940℃, holding time t 4 The fifth sintering temperature is T 5 930℃, holding time t 5 The reaction mixture was stirred for 4 hours to obtain the matrix material.

[0132] (4) The base material is subjected to roller crushing, air flow milling, and screening. During the air flow milling, the grinding pressure is set to 0.55 MPa and the classification frequency is set to 40 Hz to obtain a dissociation product.

[0133] (5) The dissociation product is reacted with Al 2 O 3 , WO 3The two mixtures were mixed evenly in a weight ratio of 100:0.2:0.3 to obtain a second mixture, and the second mixture was placed in an oxygen-containing atmosphere for secondary sintering. The secondary sintering temperature was 500° C. and the secondary sintering time was 8 h. The secondary sintered product was screened and demagnetized to obtain the positive electrode material.

[0134] The general chemical formula of the positive electrode material prepared in this embodiment is: LiNi 0.6 Co 0.1 Mn 0.3 O 2 , where the doping elements include Zr, Sr, Al and W. Since the amount of doping elements is difficult to determine accurately, it is not reflected in the chemical formula.

[0135] Example 2

[0136] The difference from Example 1 is:

[0137] Step (3) 2 CO 3 The remaining steps were the same as those in Example 1 except that LiOH was used.

[0138] Example 3

[0139] The difference from Example 1 is:

[0140] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=50:20:30, and then a hydrochloride solution of 0.2% Zr and a hydrochloride solution of 0.05% Sr and 0.05% Ca were added to the mixed solution.

[0141] The pulse sintering process in step (3) is as follows: the temperature T1 of the first sintering stage is 980°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 950°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 980°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 980°C, and the holding time t4 is 2h. 4 is 950℃, holding time t 4 The fifth sintering temperature is T 5 940℃, holding time t 5 The reaction mixture was stirred for 4 hours to obtain the matrix material.

[0142] Example 4

[0143] The difference from Example 1 is:

[0144] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=70:10:20, and then a hydrochloride solution of 0.2% Zr and a hydrochloride solution of 0.05% Sr and 0.05% Ca were added to the mixed solution.

[0145] The pulse sintering process in step (3) is as follows: the temperature T1 of the first sintering stage is 940°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 910°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 940°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 940°C, and the holding time t4 is 2h. 4 910℃, holding time t 4 The fifth sintering temperature is T 5 is 900℃, holding time t 5 The reaction mixture was stirred for 4 hours to obtain the matrix material.

[0146] Example 5

[0147] The difference from Example 1 is:

[0148] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=80:10:10, and then a hydrochloride solution of 0.2% Zr and a hydrochloride solution of 0.05% Sr and 0.05% Ca were added to the mixed solution.

[0149] The pulse sintering process in step (3) is as follows: the temperature T1 of the first sintering stage is 870°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 840°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 870°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 840°C, and the holding time t4 is 2h. 4 is 840℃, holding time t 4 The fifth sintering temperature is T 5 is 830℃, holding time t 5 The reaction mixture was stirred for 4 hours to obtain the matrix material.

[0150] Example 6

[0151] The difference from Example 1 is:

[0152] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=90:6:4, and then a hydrochloride solution of 0.2% Zr and a hydrochloride solution of 0.05% Sr and 0.05% Ca were added to the mixed solution.

[0153] The pulse sintering process in step (3) is as follows: the temperature T1 of the first sintering stage is 830°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 800°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 830°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 800°C, and the holding time t4 is 2h. 4 The temperature is 800℃, and the holding time is t 4The fifth sintering temperature is T 5 is 790℃, holding time t 5 The sintering process was continued for 4 hours to obtain a sintered product.

[0154] Example 7

[0155] Compared with Example 1, the amount of sucrose used in step (3) is 1%, and the remaining steps are consistent with Example 1.

[0156] Example 8

[0157] Compared with Example 1, the amount of sucrose used in step (3) is 5%, and the remaining steps are consistent with Example 1.

[0158] Example 9

[0159] Compared with Example 1, the pulse sintering process in step (3) is as follows: the temperature T1 of the first sintering stage is 960°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 930°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 960°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 960°C, and the holding time t4 is 2h. 4 930℃, holding time t 4 The fifth sintering temperature is T 5 920℃, holding time t 5 The sintering process was continued for 4 hours to obtain a sintered product.

[0160] Example 10

[0161] Compared with Example 1, the difference is:

[0162] The pulse sintering process in step (3) is as follows: the temperature T1 of the first sintering stage is 970°C, and the holding time t1 is 2h; the temperature T2 of the second sintering stage is 940°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 970°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 970°C, and the holding time t4 is 2h. 4 940℃, holding time t 4 The fifth sintering temperature is T 5 930℃, holding time t 5 The sintering process was continued for 4 hours to obtain a sintered product.

[0163] Embodiment 11

[0164] Compared with Example 1, the amount of pore-forming agent (polymethyl methacrylate) used in step (3) is 3%, and the remaining steps are consistent with Example 1.

[0165] Example 12

[0166] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=60:10:30.

[0167] (2) The positive electrode material precursor (Ni) was synthesized by spray pyrolysis method (dehydration temperature 500°C, pyrolysis temperature 650°C) 0.6 Co 0.1 Mn 0.3 O), the positive electrode material precursor is air flow-pulverized to obtain an oxide precursor with a particle size of D50=3.3 μm.

[0168] (3) The oxide precursor Ni 0.6 Co 0.1 Mn 0.3 O and Li 2 CO 3 According to the molar ratio of 1:1.03, Ni 0.6 Co 0.1 Mn 0.3 O and carbon powder are uniformly mixed in a mass ratio of 1:3% to obtain a first mixture, and the first mixture is subjected to pulse sintering treatment in an oxygen atmosphere with an ambient pressure of 40 Pa. The specific sintering process is as follows: the temperature T1 of the first sintering stage is 970°C, and the holding time t1 is 4h; the temperature T2 of the second sintering stage is 940°C, and the holding time t2 is 2h; the temperature T3 of the third sintering stage is 970°C, and the holding time t3 is 2h; the temperature T4 of the fourth sintering stage is 970°C, and the holding time t4 is 2h. 4 940℃, holding time t 4 The fifth sintering temperature is T 5 930℃, holding time t 5 The reaction mixture was stirred for 4 hours to obtain the matrix material.

[0169] (4) The base material is subjected to roller crushing, air flow pulverization, and screening. During the air flow pulverization, the grinding pressure is set to 0.55 MPa and the grading frequency is set to 40 Hz to obtain a positive electrode material.

[0170] Example 13

[0171] Compared with Example 1, in step (1), nickel chloride, cobalt chloride and aluminum chloride are weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Al=60:10:30.

[0172] Comparative Example 1

[0173] The difference from Example 1 is:

[0174] (1) Nickel chloride, cobalt chloride, and manganese chloride were weighed and prepared into a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=60:10:30, and then a 0.2% Zr hydrochloride solution and a 0.01% Sr hydrochloride solution were added to the mixed solution. The solution was added into a reactor at 55°C, and NaOH and NH 3 H2O was used as a precipitant and chelating agent for coprecipitation reaction for 36 hours to obtain Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 The precursor is dried at 80°C for 12 hours and then dried again at 110°C for 12 hours to obtain a hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 .

[0175] Without going to step (2), go directly to step (3):

[0176] (3) Releasing the hydroxide precursor with Li 2 CO 3 According to the molar ratio of 1:1.03, the hydroxide precursor and the sucrose are evenly mixed in the mass ratio of 1:0.2%:3% to obtain a first mixture, and the first mixture is pulse-segmented sintered under an oxygen atmosphere. The specific sintering process is as follows: the temperature T1 of the first sintering is 970°C, and the insulation time t1 is 4h; the temperature T2 of the second sintering is 940°C, and the insulation time t2 is 2h; the temperature T3 of the third sintering is 970°C, and the insulation time t3 is 2h; the temperature T4 of the fourth sintering is 930°C, and the insulation time t4 is 4h to obtain a sintered product.

[0177] The remaining steps are the same as in Example 1.

[0178] Comparative Example 2

[0179] Compared with Example 1, the amount of sucrose used in step (3) is 0%, and the remaining steps are consistent with Example 1.

[0180] Comparative Example 3

[0181] Compared with Example 1, (3) the oxide precursor and Li 2 CO 3 The oxide precursor and sucrose were mixed evenly in a molar ratio of 1:1.03 and a mass ratio of 1:3% to obtain a first mixture, and the first mixture was sintered in an oxygen atmosphere at an ambient pressure of 40 Pa, a sintering temperature of 970°C, and a holding time of 7 hours to obtain a matrix material.

[0182] Comparative Example 4

[0183] Compared with Example 1, in step (4), the base material is subjected to roller crushing, air flow milling and screening. During the air flow milling, the grinding pressure is set to 0.3 MPa and the classification frequency is set to 30 Hz to obtain a dissociation product.

[0184] Test method:

[0185] (1) Particle distribution test of positive electrode materials:

[0186] The SEM image of the positive electrode material is measured by an electron scanning electron microscope at a magnification of 3K. The total number of all particles of the positive electrode material in the SEM image is N, wherein the number of agglomerate particles formed by the agglomeration of 5 or more particles with a particle size of less than 1 μm is n; the number of agglomerates accounts for β=n / N.

[0187] Nana Measure software was used to calculate the particle size in the SEM image. More than 200 particles in the SEM image were randomly measured. The average size of the longest diameter of a single particle was D, the average size of the straight line perpendicularly bisecting the longest diameter of the particle was L, and the average aspect ratio of the particle was α=D / L. The longest length of the agglomerate was less than 4 μm.

[0188] The particle size in the SEM image was calculated using Nana Measure software, and the longest diameter of the primary particles was measured to be the particle size of the primary particles, and the particle size of the primary particles was 1 μm to 5 μm.

[0189] (2) Test of metal element content in positive electrode materials:

[0190] The content of various metal elements in the positive electrode material was tested by ICP. The element content in the material was analyzed using an Agilent 5800 ICP spectrometer. The specific operation steps were as follows: 0.4 g of ternary positive electrode material was added to a conical flask, and then 60 mL of pure water and 8 mL of aqua regia were added. The flask was placed on a graphite heating platform and digested at 375 ° C until it was clear. The obtained solution was diluted to 100 mL using a volumetric flask and sampled for dilution, and then the diluted solution was analyzed for composition.

[0191] (3) Particle size test:

[0192] The particle size distribution of the positive electrode material particles was obtained by using the laser diffraction light intensity distribution of the British Malvern Mastersizer 3000 model laser particle size analyzer. The volume-based cumulative particle size distribution of the particle size distribution determination was measured by the laser diffraction method, D 10 It indicates the particle size corresponding to the cumulative particle size distribution percentage of the powder reaching 10%, D 50Indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D 90 It indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%.

[0193] Volume particle size distribution width of positive electrode material = (D 90 -D 10 ) / D 50 .

[0194] (4) Specific surface area test of positive electrode materials:

[0195] The specific surface area of ​​the material was calculated using the American TriStar II specific surface and pore analyzer by nitrogen adsorption and the BET method.

[0196] (5) Morphology test:

[0197] The Hitachi S4800 scanning electron microscope was used to observe the surface morphology, particle size, etc. of the samples, and the SEM image of the positive electrode material was obtained.

[0198] (6) Tap density test of positive electrode material:

[0199] Test of tap density ρ1: Dandong Better BT-303 was used to test the tap density, with a vibration rate of 3000 times / min, a vibration time of 1min, and a vibration amplitude of 3mm±0.1mm.

[0200] (7) Compacted density test of positive electrode materials:

[0201] The compaction density ρ2 of the powder was tested using a compaction density meter with a pressure of 6t for 30s.

[0202] (8) Electrochemical performance evaluation using button half-cell:

[0203] The positive electrode material: conductive agent SP: binder (PVDF glue) = 93:5:2 mass ratio was mixed and homogenized, and then the slurry was evenly coated on a 16μm thick aluminum foil and placed in a 100℃ oven for drying for 12h. The negative electrode used a Li metal sheet with a diameter of 16mm and a thickness of 1mm, the diaphragm used a polyethylene porous membrane with a thickness of 20μm, and the electrolyte used an equal amount of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1mol / L LiPF6 as the electrolyte. The positive electrode sheet, diaphragm, negative electrode sheet and electrolyte were assembled into a 2016 button battery in an Ar gas glove box with a water content and an oxygen content of less than 5ppm.

[0204] Capacity test system: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 2.8 ~ 4.4V, temperature condition is 25 ℃), 0.1C charge, 0.1C discharge, constant voltage cut-off current is 0.005C, and the discharge capacity C mAh / g is calculated based on the discharge capacity.

[0205] Cycle test system: at 25℃, charge and discharge voltage of 2.8-4.4V, 0.5C charge and 1C discharge, 50 cycles, constant voltage cutoff current of 0.05C, the final capacity retention rate after 50 cycles is the cycle performance.

[0206] The test results of Examples 1 to 13 (abbreviated as S1 to S13) and Comparative Examples 1 to 4 (abbreviated as D1 to D4) prepared in the present application are detailed in Tables 1 to 2.

[0207] Table 1 Physical and chemical performance parameters of positive electrode materials

[0208]

[0209] Table 2 Electrochemical performance results of positive electrode materials

[0210]

[0211]

[0212] like Figure 2 The SEM image of the positive electrode material prepared in Example 1 is shown in FIG. Figure 2 It can be seen that in the particles of the positive electrode material prepared in Example 1, the number of agglomerates is 0, the particles have a high degree of roundness and good dispersibility.

[0213] like Figure 3 As shown, it is the SEM image of the positive electrode material prepared in Comparative Example 1. Figure 3 It can be seen that in the particles of the positive electrode material prepared in Comparative Example 1, the number of agglomerates is relatively large and the roundness of the particles is relatively low.

[0214] According to the test data of the embodiment, the oxide precursor, lithium source, dopant and pore former are mixed. The addition of pore former is conducive to the precursor to fully contact with oxygen during the sintering process, accelerate the reaction rate, improve the looseness of the matrix material, reduce the degree of agglomeration of particles, and greatly reduce the proportion of agglomerates in the positive electrode material. At the same time, the particle roundness can also be improved. At the same time, a segmented sintering process is adopted. Due to the short high-temperature sintering time, the particles tend to grow uniformly. The matrix material obtained by sintering is subjected to dissociation treatment, and some agglomerates formed by agglomeration of 2 to 3 particles can be re-dissociated into single particles during the dissociation treatment process, which can reduce the proportion of agglomerates in the positive electrode material. At the same time, the average aspect ratio of the particles in the positive electrode material is controlled within the range of 1 to 1.6, which can improve the tolerance and structural order of the particles of the positive electrode material, so that the compaction density and capacity of the positive electrode material are improved, and the long cycle performance of the positive electrode material can also be improved.

[0215] Comparing Example 1 with Examples 2 to 6, under the premise of keeping the same process conditions, only the lithium source or different oxide precursors are replaced, and the electrochemical performance of the prepared positive electrode material is still at a high level. The capacity and cycle performance of the positive electrode material are mainly affected by the content of the Ni element. And as the nickel content in the positive electrode material increases, the primary sintering temperature increases, and the degree of agglomeration of the particles will also increase slightly.

[0216] Compared with Example 7, after reducing the amount of pore-forming agent sucrose used, the degree of contact between oxygen and precursor material during sintering is reduced, the particle growth is affected, the aspect ratio α of the particles becomes larger, the roundness decreases, the capacity of the positive electrode material is improved, but the cycle performance is slightly reduced after a long cycle.

[0217] Compared with Example 1 and Example 8, after increasing the usage of the pore-forming agent sucrose, oxygen is in more complete contact with the precursor material during sintering, the particles grow more rounded, and the aspect ratio α value decreases, indicating that the number of slender particles in the particles is reduced, and the particle size distribution width of the positive electrode material is reduced, resulting in a decrease in the compaction density of the positive electrode material, and a slight decrease in the overall capacity and cycle of the positive electrode material.

[0218] Compared with Example 9, in the preparation process, the pulse sintering temperature decreased, the particle size D50 was reduced compared with that of Example 1, the proportion of agglomerates in the positive electrode material increased slightly, and the capacity and cycle performance of the positive electrode material were slightly affected.

[0219] Compared with Example 10, during the preparation process, after the pulse sintering time is shortened, the particles grow insufficiently, resulting in a slight increase in the proportion of agglomerates in the positive electrode material, a wider particle size distribution of the positive electrode material, and an increased compaction density of the positive electrode material. However, the capacity and cycle performance of the positive electrode material are slightly reduced.

[0220] Compared with Example 1 and Example 11, the use of different types of pore-forming agents can effectively alleviate the degree of particle agglomeration, thereby reducing the proportion of agglomerates in the positive electrode material. At the same time, it can also improve the roundness of the particles, which is beneficial to improving the capacity and cycle stability of the positive electrode material.

[0221] Compared with Example 12, the positive electrode material is not doped or coated with other metal elements, the roundness of the particles deteriorates during the growth process, and the aspect ratio increases; since no secondary sintering treatment is performed, the cycle performance of the positive electrode material also decreases.

[0222] Compared with Example 1, Example 1 prepares the positive electrode material hydroxide precursor by coprecipitation method. The roundness of the positive electrode material is reduced, the particle edges are obvious, the degree of agglomeration is increased, and fine powder is more likely to be produced in the subsequent dissociation treatment. The cycle performance of the positive electrode material is significantly reduced.

[0223] Compared with Example 1 and Comparative Example 2, after no pore-forming agent is added in Comparative Example 2, the oxygen atmosphere of the oxide precursor particles during the sintering process is affected, the aspect ratio of the particles increases, and the roundness of the particles decreases, resulting in excessive local expansion stress of the particles during the cycle, the particles are easily broken, the side reactions between the positive electrode material and the electrolyte increase, and the cycle retention rate of the positive electrode material decreases.

[0224] Compared with Example 1 and Comparative Example 3, Comparative Example 3 adopts ordinary sintering, the growth rate and oxygen atmosphere of the particles become worse, the aspect ratio of the particles increases significantly, the agglomerates also increase significantly, and the capacity and cycle of the positive electrode material are significantly reduced.

[0225] Compared with Example 1 and Comparative Example 4, the grinding air pressure during the airflow crushing of the positive electrode material of Comparative Example 4 is smaller, and the classification frequency is also smaller, resulting in that some agglomerates cannot be effectively dissociated, resulting in an increase in the number of agglomerates in the positive electrode material, and the capacity and cycle performance of the positive electrode material are also reduced.

[0226] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes a plurality of particles and aggregate particles; The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, the total number of particles of the positive electrode material in the SEM image is N, N ≥ 200, wherein the number of agglomerate particles formed by agglomeration of 5 or more particles with a particle size of less than 1 μm is n; The number ratio of the agglomerates β=n / N, β≤1%; More than 200 particles in the SEM image are randomly measured, the average size of the longest diameter of the particles is D, the average size of the straight line side perpendicularly bisecting the longest diameter of the particles is L, and the average aspect ratio of the particles is α=D / L, 1<α<1.

6.

2. The positive electrode material according to claim 1, characterized in that 2.0μm<D<3.0μm; 1.5μm≤L≤2.5μm.

3. The positive electrode material according to claim 1 or 2, characterized in that The chemical formula of the positive electrode material is Li k Ni a Co b N c M d O2, 0.98≤k≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, and the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La and Ce.

4. The positive electrode material according to claim 1, characterized in that The volume median particle size D of the positive electrode material 50 3.0 μm to 5.0 μm; and / or, the volume particle size distribution width of the positive electrode material satisfies: 1.0<(D 90 -D 10 ) / D 50 <1.

5.

5. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, the particles include primary particles, the primary particles have the same orientation, and the particle size of the primary particles is 1 μm to 5 μm.

6. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The specific surface area of ​​the positive electrode material is Sm 2 / g, 0.5<S<0.9; (2) The tap density of the positive electrode material is ρ1g / cm 3 , 1.8<ρ1<2.5; (3) The compaction density of the positive electrode material is ρ2g / cm 3 , 3<ρ2<3.5; (4) The longest length of the agglomerates is less than 4 μm.

7. A method for preparing a positive electrode material, characterized in that: The preparation method comprises: Mixing an oxide precursor, a lithium source, a dopant and a pore former to obtain a first mixture, wherein the amount of the pore former added is 1% to 5% based on the mass of the oxide precursor being 100%; In an oxygen-containing atmosphere, the first mixture is pulse sintered to obtain a matrix material, wherein the pulse sintering process includes a first stage, a second stage, the first stage and the second stage, and a fifth stage which are performed in sequence, the sintering temperature T1 of the first stage is 800°C to 1000°C, the sintering temperature T2 of the second stage is T1-30°C, and the sintering temperature T5 of the fifth stage is T2-10°C; the holding time of the T1 temperature is controlled to be 4h to 8h; The base material is subjected to a dissociation treatment, and the dissociation product is mixed with a coating agent and then subjected to a secondary sintering treatment to obtain a positive electrode material.

8. The preparation method according to claim 7, characterized in that: The preparation method meets at least one of the following characteristics: (1) The general chemical formula of the oxide precursor is Ni x Co y N z O2, wherein 0.50≤x≤0.98, 0<y≤0.20, 0<z≤0.35, 0≤e≤0.05, x+y+z+e=1, and N is Mn or Al; (2) Based on the mass of the oxide precursor being 100%, the amount of the dopant added is 0.05% to 0.4%; (3) The ratio of the molar amount of Li in the lithium source to the total molar amount of the transition metal in the oxide precursor is 1.0≤n Li / n Me ≤1.06; (4) The dopant comprises a compound containing an element M, wherein the element M comprises at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Y, B, Nb, W, Sb, Ta, Sn, Mo, La and Ce; (5) The pore-forming agent includes at least one of carbon powder, sucrose, starch, pine powder, polyvinyl alcohol, polymethyl methacrylate, polyethylene glycol and coal powder; (6) The lithium source includes at least one of lithium hydroxide, lithium oxide, lithium carbonate, lithium nitrate, lithium acetate, lithium phosphate and lithium oxalate.

9. The preparation method according to claim 7, characterized in that: The method satisfies at least one of the following characteristics: (1) The dissociation treatment includes at least one of roller crushing, mechanical crushing, air flow crushing and micron-sized particle dissociation; (2) The dissociation treatment includes air flow milling, and the grinding pressure of the air flow milling is 0.3Mpa to 0.8Mpa; (3) The dissociation treatment includes air flow pulverization, and the classification frequency of the air flow pulverization is 30 Hz to 55 Hz; (4) The secondary sintering treatment is performed at a temperature of 350°C to 600°C and for a time of 5h to 10h.

10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Single crystal type multi-element positive electrode material, preparation method thereof and lithium ion battery

    CN116169261A

  • Single crystal type sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

    CN117810437A

Cited By

  • Positive electrode material and positive electrode sheet comprising same, and battery

    WO2026138633A1